1969
DOI: 10.1104/pp.44.12.1724
|View full text |Cite
|
Sign up to set email alerts
|

Relation of CO2 Compensation Concentration to Apparent Photosynthesis in Maize

Abstract: ,1u CO2/l air) for species with inefficient photosynthesis and high photorespiration, and low (<10 pI CO2/l air) for species with efficient photosynthesis and negligi-ble photorespiration (4,16,25,26).Maize belongs to this latter group (14, 16), and has a rCO2L, independent of°2 concentration (15,20).Recent models demonstrate that the magnitude of the [CO2], depends upon the diffusive resistance of the leaf to CO2, the efficiency of CO2 fixation in the chloroplasts, and the respiration rate of the leaf (1,21,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It has been suggested that compensation point is the level of C0 2 at which gross photosynthesis and photorespiration just balance one another (Heichel and Musgrave 1969). It has been suggested that compensation point is the level of C0 2 at which gross photosynthesis and photorespiration just balance one another (Heichel and Musgrave 1969).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that compensation point is the level of C0 2 at which gross photosynthesis and photorespiration just balance one another (Heichel and Musgrave 1969). It has been suggested that compensation point is the level of C0 2 at which gross photosynthesis and photorespiration just balance one another (Heichel and Musgrave 1969).…”
Section: Resultsmentioning
confidence: 99%
“…The high affinity for CO2 in maize leaves could be caused by the nature of the irreversible reaction which is involved in feeding the CO2 reserve (24,27). Thus a possible explanation of the low compensation point found in maize (10,23,30) …”
mentioning
confidence: 99%
“…The SLAVR is a measure of leaf area per unit of leaf dry weight and is negatively associated with the rate of photosynthesis. This has been shown for several crops, including alfalfa (Medicago sativa L.) (Pearce et al, 1969), maize (Heichel and Musgrave, 1969), soybean (Dornhoff and Shibles, 1976), oat (Avena sativa L.) (Criswell and Shibles, 1971) Figure 2. Effects of changing the number of photothermal days from emergence to fl owering (EMFL) and the number of photothermal days from fi rst seed to physiological maturity (SDPM) simultaneously in opposite direction (a and b) in Step 1 and changing the number of photothermal days from fi rst fl owering to end of leaf expansion (FLLF) (c and d) in Step 2 on fi nal biomass and seed yield averaged over 10 locations, three growing seasons, and 30 yr .…”
Section: Adjustment Of Growth Parametersmentioning
confidence: 76%
“…Second, the realizable gain from higher LFMAX could be less than Fig. 3 indicates because increased LFMAX has been reported to be positively associated with decreased SLAVR (Irvine, 1967;Heichel and Musgrave, 1969;Pearce et al, 1969;Criswell and Shibles, 1971;Dornhoff and Shibles, 1976;Wright et al, 1988), so there is a partial confl ict of simultaneous increases in both SLWVR and LFMAX. Analyses by Boote et al (2003) illustrate the importance of considering photosynthesis increases, with coupling or uncoupling of LFMAX to SLAVR.…”
Section: Adjustment Of Growth Parametersmentioning
confidence: 93%
See 1 more Smart Citation